2008
DOI: 10.1590/s1516-14392008000200020
|View full text |Cite
|
Sign up to set email alerts
|

High temperature oxidation behavior of the AISI 430A and AISI 430E stainless steels in Ar/H2/H2O atmosphere

Abstract: The high temperature oxidation behavior of two ferritic stainless steels type AISI 430A and AISI 430E is examined at low oxygen pressure and high temperatures. The AISI 430A steel is ferritic up to 860 °C. Above this temperature, this steel is bi-phased: presence of austenite and ferrite phases. The 430E steel is stabilized with Nb, and is ferritic at all temperatures. The oxidation experiments were performed in a thermobalance SETARAM TGDTA 92, in the range of 850-950 °C, in Ar/H 2 /H 2 O atmosphere, under ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
2
5
0
3
Order By: Relevance
“…The oxide scale growth rate is calculated by Equation 1, where M is the sample mass gain, A is the sample surface area, t is the oxidation time and Kp is the parabolic rate constant. The result of parabolic rate constant (Kp) ( Table 4) of the bare sample is consistent with values presented in studies in the literature [31][32][33] . It is observed that the Kp results (Table 4) are similar for all the samples, which demonstrate that the formation of oxide was not influenced by the difference in surface samples.…”
Section: Resultssupporting
confidence: 90%
“…The oxide scale growth rate is calculated by Equation 1, where M is the sample mass gain, A is the sample surface area, t is the oxidation time and Kp is the parabolic rate constant. The result of parabolic rate constant (Kp) ( Table 4) of the bare sample is consistent with values presented in studies in the literature [31][32][33] . It is observed that the Kp results (Table 4) are similar for all the samples, which demonstrate that the formation of oxide was not influenced by the difference in surface samples.…”
Section: Resultssupporting
confidence: 90%
“…The spheres were smaller than 10 μm. The similar spinels forming spheres in the oxidized layer on ferrite steel were observed by [15]. The authors, taking into consideration of the increased content of Cr, Mn and O defined the spinels as MnCr 2 O 4 .…”
Section: Tests Results Of the Microstructure And Chemical Compositionsupporting
confidence: 63%
“…Dessa forma uma grande quantidade de cromo é removida de uma faixa relativamente estreita, deixando regiões dos contornos de grãos (empobrecidas) que podem ficar com até 2% de cromo a menos [7]. Tal fenômeno foi observado por Salgado [6], ao afirmar que a microestrutura dos filmes formados sobre o aço AISI 430A, oxidado em atmosfera de argônio, por 50 h, também apresentou o mesmo comportamento, para temperatura de 850 °C. Já a 950 °C a microestrutura apresenta partículas contendo cromo, ou seja, mesmo a 950 °C houve formação de filme aderente de óxido de cromo sobre o aço, apesar da ocorrência de perda de massa por unidade de área.…”
Section: Análise Microestrutural E Composicional Dos óXidos Formadosunclassified
“…Em todos os meios onde há presença de oxigênio o aço está sujeito a oxidação, mesmo em atmosfera protetora como é o caso do gás argônio contendo 1ppm de O 2 , suficiente para causar oxidação no aço [6].…”
Section: Introductionunclassified